TATA CARA PERHITUNGAN, PENYETORAN, PELAPORAN, DAN PENCATATAN PPN PADA PT XYZ - Bodhi, Ananda; Sukadana, Ida Bagus Nyoman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted with the aim of analyzing the practice of calculating, depositing, reporting and recording value added tax at PT XYZ in 2022 with the provisions of the VAT Law no. 42 of 2009, PMK no. 242/PMK.03/2014, PMK Number 18/PMK.03/2021, Law no. 7 of 2021, and generally applicable tax accounting principles. The form of this research is qualitative descriptive analysis research. Data obtained from internship activities for the purposes of preparing this research include Tax Invoices, Periodic VAT Notification Letters with attachments, Proof of VAT Deposits, Proof of VAT Reporting, and Recording Journals obtained directly from PT XYZ. The results of this research explain that PT XYZ as a whole carries out procedures for calculating, depositing, reporting and recording VAT in accordance with VAT Law no. 42 of 2009, PMK no. 242/PMK.03/2014, PMK Number 18/PMK.03/2021, Regulation of the Director General of Taxes Number PER-02/PJ/2019, Law no. 7 of 2021, and generally applicable tax accounting principles.